Biogated mesoporous silica nanoagents for inhibition of cell migration and combined cancer therapy - Wu, Yu; Shi, Xiao-Jie; Dai, Xin-Yi; Song, Tian Shun; Li, Xiang-Ling; Xie, Jing Jing (Mikrochimica acta (1966), 2024)
Migration is an initial step in tumor expansion and metastasis; suppressing cellular migration is beneficial to cancer therapy. Herein, we designed a novel biogated nanoagents that integrated the migration inhibitory factor into the mesoporous silica nanoparticle (MSN) drug delivery nanosystem to realize cell migratory inhibition and synergistic treatment. Antisense oligonucleotides (Anti) of microRNA-330-3p, which is positively related with cancer cell proliferation, migration, invasion, and angiogenesis, not only acted as the locker for blocking drugs but also acted as the inhibitory factor for suppressing migration via gene therapy. Synergistic with gene therapy, the biogated nanoagents (termed as MSNs-Gef-Anti) could achieve on-demand drug release based on the intracellular stimulus-recognition and effectively kill tumor cells. Experimental results synchronously demonstrated that the migration suppression ability of MSNs-Gef-Anti nanoagents (nearly 30%) significantly contributed to cancer therapy, and the lethality rate of the non-small-cell lung cancer was up to 70%. This strategy opens avenues for realizing efficacious cancer therapy and should provide an innovative way for pursuing the rational design of advanced nano-therapeutic platforms with the combination of cancer cell migratory inhibition. Graphical abstract